Do PROMIS Scores Show That Nonoperative Treatment of Achilles Tendonopathy Works?. Issue 3 (11th September 2017) - Anderson, Michael; Bernstein, David; Baumhauer, Judith; Flemister, Adolph; Ketz, John; Oh, Irvin; DiGiovanni, Benedict
Category: Ankle, Sports Introduction/Purpose: Achilles tendonopathy (AT), whether insertional (IAT) or non-insertional (NIAT), is a common clinical disorder. Operative and nonoperative care have been evaluated, although often employing non-validated measures. In addition, it is common for AT response to be reported without separating IAT versus NIAT. This adds to uncertainty regarding expected improvement in patients presenting for treatment with AT. There is a paucity of literature analyzing nonoperative treatment of IAT and NIAT as distinct entities using patient-reported outcomes. We utilize Patient-Reported Outcomes Measurement Information System (PROMIS) Physical-Function (PF), Pain-Interference (PI) and Depression (D) domains to determine clinical response to nonoperative treatment in all AT patients. We further compared clinical response in patients with IAT to patients with NIAT. Methods: Patient visits to an academic orthopaedic foot and ankle center over an 18 month period (March 2015 to October 2016) were prospectively collected. All patients with AT were determined using ICD-9 codes, and they were stratified between IAT and NIAT. Only patients with complete PROMIS scores (PF, PI and D) at both presentation as well as following a course of nonoperative care, including heel lifts and an achilles/gastrocnemius stretching and strengthening program, were included for analysis. A total of 102 patients fit our inclusion criteria, with an average follow up of 68 days. Based on a distribution-based method, the minimum clinically important difference (MCID) was set at one-half standard deviation. Overall descriptive statistics were determined for all patients. Bivariate analysis was conducted to compare NIAT and IAT patients across a wide range of variables. Significance was set at 0.05 for all analyses. Results: Fifteen (46%), 12 (36%) and 9 (27%) patients with NIAT reached MCID for PF, PI and D, respectively. Eleven (33%) patients with NIAT reached MCID in both PF and PI. Seventeen (25%), 20 (29%) and 22 (32%) patients with IAT reached MCID for PF, PI and D, respectively. Six (9%) patients with IAT reached MCID in both PF and PI. A larger percentage of men had NIAT (63.6% vs. 36.2%; p = 0.009), while a larger percentage of women had IAT (63.8% vs. 36.4%; p = 0.009). Changes in PROMIS PF scores were higher in patients with NIAT (4.0 vs. -0.046; p = 0.035). A higher percentage of patients with NIAT reached MCID in PF (45.5% vs. 24.6%; p = 0.034). Conclusion: A considerable portion of patients with AT respond favorably to nonoperative care. PROMIS scores did not vary at presentation between IAT and NIAT, yet between 25% and 46% of patients in each subgroup reached MCID in at least one domain. Although a higher percentage of patients with NIAT reached MCID, patients with IAT also demonstrated MCID improvement. Using PROMIS for disease specific pathologies and nonoperative treatment in foot and ankle care provides clinical value previously uncaptured. Our results demonstrate nonoperative treatment for AT has clinical utility and economic value in a time of increased scrutiny on healthcare spending.